2015
DOI: 10.1186/s40064-015-1496-3
|View full text |Cite
|
Sign up to set email alerts
|

The demographics of patients affected by surgical disease in district hospitals in two sub-Saharan African countries: a retrospective descriptive analysis

Abstract: BackgroundThere is a growing awareness of the importance of surgical disease within global health. We hypothesised that surgical disease in low income countries predominantly affects young adults and may therefore have a significant economic impact.MethodsWe retrospectively reviewed all surgical admission data from two rural government district hospitals in two different sub-Saharan African countries over a 6-month period. We analysed all surgical admissions with respect to patient demographics (age and gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The age profile of surgical patients in both countries indicates that trauma and general surgical procedures are most commonly undertaken on the youngest sections of the population that have not yet entered the labour market , and also in the economically productive age groups. This corresponds with research from Malawi and Sierra Leone and the global burden of disease . However, almost overshadowed by the high burden of emergency obstetric surgery was the remarkably high proportion of trauma procedures in 0‐ to 15‐year‐old girls and boys, accounting for 65% of all selected trauma cases in Malawi and 57% in Zambia.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The age profile of surgical patients in both countries indicates that trauma and general surgical procedures are most commonly undertaken on the youngest sections of the population that have not yet entered the labour market , and also in the economically productive age groups. This corresponds with research from Malawi and Sierra Leone and the global burden of disease . However, almost overshadowed by the high burden of emergency obstetric surgery was the remarkably high proportion of trauma procedures in 0‐ to 15‐year‐old girls and boys, accounting for 65% of all selected trauma cases in Malawi and 57% in Zambia.…”
Section: Discussionsupporting
confidence: 76%
“…In the absence of population data, surgical BoD estimates rely on hospital admission data and modelling . While evidence is emerging on the types of surgical procedures performed in rural SSA , there is a lack of data on the demography of those who undergo surgical procedures in such settings , in part due to the lack of reliable data collection systems at district hospitals, where much of the basic emergency and common elective surgery takes place .…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has demonstrated the feasibility of surgical outcomes audit in low-income countries. 28,34 A pragmatic continent-wide quality improvement programme may improve the allocation of resources towards the postoperative surveillance of patients most at risk. A simple surgical risk calculator may facilitate this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Burns were the fourth most common reason for presentation and third most common cause of injury in children but no burns surgery was carried out due to lack of surgical facilities. A retrospective study looking at admissions to Bo government hospital, in Sierra Leone’s second biggest city after Freetown also found that burns were a common cause for admission in the under 5 age-group [27] and burns prevalence is estimated at 4%, most frequently reported in the 0–4 age group [28] . Burns are a frequent cause of morbidity and mortality amongst young patients in low-income countries in association with poverty and crowded living conditions, mostly occurring at home due to hot liquids and open flames [29] .…”
Section: Discussionmentioning
confidence: 99%